PARTISIPASI MASYARAKAT DALAM UPAYA PENERAPAN 5 PILAR SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DI DESA CILELLANG KECAMATAN MALLUSETASI KABUPATEN BARRU - Asrijun Juhanto; Sri Suprawati; Muhammad Rifai (UNM Environmental Journals, 2022)
Community participation in implementing the 5 pillars of community-based total sanitation is very important so that it can be fully implemented so that people can live clean and healthy so as to avoid environmental-based diseases. The aim of the study was to determine Community Participation in Efforts to Implement the 5 Pillars of Community-Based Total Sanitation (STBM) in Cilellang Village, Mallusetasi District, Barru District. The type of research used is quantitative research with a quantitative descriptive approach with a total sample of 60 people taken by simple random sampling technique. The variables studied were participation and implementation of the 5 pillars of community-based total sanitation. The results of this study were based on statistical tests obtained by the Cilelleng Village Community who participated by 60.0% and 40.0% who did not participate. This research suggests the local government to socialize more about the importance of the 5 pillars in everyday life to avoid various kinds of environmental-based diseases.